Hematite‐Based Water Splitting with Low Turn‐On Voltages1. Issue 48 (7th October 2013) - Du, Chun; Yang, Xiaogang; Mayer, Matthew T.; Hoyt, Henry; Xie, Jin; McMahon, Gregory; Bischoping, Gregory; Wang, Dunwei
<x xml:space="preserve">Abstract</x> Power up: The photoelectrochemical performance of hematite in a water‐splitting device was improved significantly through surface modification with amorphous NiFeOx (see graph showing the large cathodic shift observed; FTO=fluorine‐doped tin oxide). The measured photovoltage increased from 0.24 to 0.61 V, which yielded a record‐low turn‐on potential of 0.62 V (versus the reversible hydrogen electrode, RHE).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>